″Topicality and requirements of the labor market in regard to professional training of future specialists of the motor transport industry″. - Kozlovskiy Yu. М.; Pukalo M. І. (Problems of Engineer-Pedagogical Education, 2018)
The article substantiates the problem of competitiveness of motor transport enterprises and provides the results of the analysis of the current state of demand and supply on the motor transport market in the group of enterprises of the Lviv and Zhytomyr regions. In order to determine whether the number of workers employed by each of the investigated enterprises is sufficient or nor, a statistical analysis of working time of the employees was carried out. It was revealed that there exists a growing need for specialists in the motor transport sphere and the motor vehicle service in particular. The parameters for ensuring the quality of service provision are highlighted; the criteria for assessing the work of a service station are selected. The reasons for "ignoring" the modern principles of the implementation of an adequate level of the quality of motor vehicle services are provided. The article also analyzes competences of future specialists in the motor transport sphere. The problems of training future specialists under the conditions of educational institutions are singled out. The paper considers some innovative means, e.g. automated design systems, which allow creating objects using a set of elementary parametric bodies, as well as the possibility of three-dimensional modeling.